Seismic performance of concrete dam-reservoir system - H.Humaish, Asad; S.Shamkhi, Mohammed; K. Al-Hachami B. Sc, Thulfiqar (International Journal of Engineering and Technology, 2019)
This research is devoted to experimental work on the dynamic response of concrete gravity dam (small scale model under 1-g) taking into account the dam-reservoir and the dam-foundation interaction using the earthquake simulator shaking table which was designed and manufactured for this purpose. A 1-g dam model tests are performed and the soil foundation underneath the dam model was prepared using an air pluviation technique to obtain the relative density of 55% (medium dense soil). Many specific instruments were used: accelerometers, lvdts, pore water pressure and dynamic water pressure to measure different parameters during shaking. Two cases of tests were conducted: i) Dam built on saturated cohesion-less soil (test-1) and ii) The filled with water dam model (test-2). The seismic behavior is investigated during shaking (i.e. dynamic response and the seismic displacement) and the failure mechanism is inspected during the shaking. It was concluded that the case where the dam was filled with water is more stable during shaking that the other case and the failure mechanism is totally different. (I.e. sliding and overturning failure). The acceleration response spectra and the pore water pressure are measured and analyzed as well.Â Â